2020
DOI: 10.1371/journal.pone.0239310
|View full text |Cite
|
Sign up to set email alerts
|

Stigma toward small babies and their mothers in Ghana: A study of the experiences of postpartum women living with HIV

Abstract: Infants born to HIV-infected mothers are more likely to be low birthweight (LBW) than other infants, a condition that is stigmatized in many settings worldwide, including sub-Saharan Africa. Few studies have characterized the social-cultural context and response to LBW stigma among mothers in sub-Saharan Africa or explored the views of women living with HIV (WLHIV) on the causes of LBW. We purposively sampled thirty postpartum WLHIV, who had given birth to either LBW or normal birthweight infants, from two ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Parents face an enormous cost burden [17] coupled with having to conform to popular sector beliefs and harmful practices propelled by Ghanaian culture and religion [18]. Premature babies are frowned upon and so mothers may not seek for or receive adequate support for fear of stereotypical attitudes [18,19]. Often many preterm babies are readmitted in a critical state and particularly those born extremely preterm die at home [15].…”
Section: Introductionmentioning
confidence: 99%
“…Parents face an enormous cost burden [17] coupled with having to conform to popular sector beliefs and harmful practices propelled by Ghanaian culture and religion [18]. Premature babies are frowned upon and so mothers may not seek for or receive adequate support for fear of stereotypical attitudes [18,19]. Often many preterm babies are readmitted in a critical state and particularly those born extremely preterm die at home [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have widely discussed the psychosocial traumas faced by mothers whose babies were admitted in neonatal wards (Al Maghaireh et al, 2016; Garti et al, 2021). The risk of neglect due to stigma and shame have been well established (Sakyi et al, 2020; Smith et al, 2017). Like our findings, in Malawi and Ethiopia, the use of success stories had positive impact on families with LBW infants and when complemented with early counselling could change negative perceptions and stigma in communities (Lydon et al, 2018; Usman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of LBW infants are often constrained by finances, work and the responsibility of caring for their vulnerable babies. Others have reported on inadequate maternal support and economic challenges faced by mothers post‐delivery (Sakyi et al, 2020; Unsworth et al, 2021). Similar to the needs and responsibilities our participants highlighted, in a recent Ghanaian study, women of preterm babies reported on practical (domestic chores/baby care), material, psychosocial and spiritual support (Tibil & Ganle, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is also no support to overcome social pressures, stigma and other barriers in the community and family settings that affect survival of preterm infants [ 9 ]. Studies have discussed the issue of stigma related to small babies and preterm babies in sub-Saharan Africa, which can have a detrimental effect on the ability of the parents to care for the baby, as well as affect their own health and wellbeing [ 10 ]. For example, a study from Malawi found that in some communities, a premature baby is equated to having an abortion and was therefore perceived as “a curse” [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study from Malawi found that in some communities, a premature baby is equated to having an abortion and was therefore perceived as “a curse” [ 11 ]. In a study in Ghana, stigma was linked to “undesirable” physical features by people who were unfamiliar with small babies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%